Phytochemistry and bioactivity studies of cassia singueana del. and c. sieberiana dc. (fabaceae) - Jibril, Saidu (2017)
Cassia singueana Del. and C. sieberiana DC. are medicinal plants used for treating diabetes, ulcer, malaria, and wound healing and also used as poison by hunters in Africa. This study discuss the phytochemicals and bioactivity of the root and leaf of C. singueana Del. and C. sieberiana DC. Extraction of the plant samples by maceration in n-hexane, ethyl acetate, and methanol sequentially, followed by fractionation and purification using various chromatographic techniques led to the isolation of twenty compounds. Structural elucidation of these compounds using spectroscopic methods enabled the identification of seven anthraquinones, four flavonoids, three stilbenes, three terpenes, one bianthrone, one xanthone, and a benzoic acid derivative. C. singueana root extract afforded islandicin, xanthorin, monodictyxanthone, 3-hydroxy-5-methoxystilbene, and 4-hydroxybenzoic acid, which were reported for the first time from Cassia genus, while C. sieberiana root extract gave a new compound, cassiberianol A. The efficiency of ultrasonic assisted extraction (UAE) was optimised using response surface methodology (RSM) for high extraction yield from the root of C. singueana. The Box-Behnken design (BBD) was employed to propose optimised UAE conditions of time (25 min), temperature (50ºC), and solvent-sample ratio (10 mL/g) for high extraction yield. The ability of the BBD model equation for predicting the optimum yield was verified and the predicted yield (1.64%) was in good agreement with the experimental yield (1.65 ± 0.07%). This agreement indicated the suitability of the model and also the success of using RSM in optimising UAE conditions for root of C. singueana. The extraction yield (1.65 ± 0.07%) obtained under the optimised UAE conditions resulted in two-fold improvement when compared to yield obtained by maceration (0.71 ± 0.60%) or Soxhlet extraction (0.79 ± 0.40%) techniques. The RSM was successfully used to optimise UAE conditions for improved efficiency of UAE over maceration and Soxhlet extraction techniques. Bioactivity screenings which include antioxidant, a-glucosidase, acetylcholinesterase, tyrosinase, and 15-lipoxygenase inhibitory activities were conducted on the crude extracts and pure compounds. The results revealed that the ethyl acetate extract from the root of C. sieberiana was the most potent DPPH radical scavenger (1.88 µg/mL), and also gave the highest total phenolic (927 mg gallic acid equivalent/g) and total flavonoid content (346 mg quercetin equivalent/g). The ethyl acetate extract from the root of C. singueana also displayed the strongest ferric reducing power (2298 µmol Fe2+/g dry weight). Meanwhile, the methanol extract from the leaf of C. singueana demonstrated the most effective ß-carotene bleaching activity (87.05%). Quercetin and piceatannol showed broad spectrum of inhibitory activities against a-glucosidase (IC50 5.73 and 7.37 µM, respectively), acetylcholinesterase (IC50 2.89 and 10.57 µM, respectively), tyrosinase (IC50 92.40 and 95.14%, respectively), and 15-lipoxygenase (IC50 0.98 and 1.27 µM, respectively) compared to the positive controls used in these assays. However, physcion highly suppressed the activity of tyrosinase enzyme (79.66%), while cassiberianol A showed significant inhibition (IC50 2.63 µM) towards 15-lipoxygenase enzyme. The significant bioactivities demonstrated by the polar extracts from C. singueana and C. sieberiana can be attributed to the presence of phytochemicals such as flavonoids and stilbenes isolated from these polar extracts.